Numerical Analysis of Chinese Economy in an Small Scale RBC Model: 1996-2005 - Li Li; Yang Liu (2009 International Conference on Advanced Computer Control, 2009)
This paper uses a version of Hansen's (1985) real business cycle (RBC) model to mimic Chinese business cycle from 1996 to 2005. The comparison of simulation results and actual data implies that the model can reflect economic fluctuations. Quantitative analysis demonstrates that technology shock contributes to more than 90.3% of Chinese economic fluctuations, and RBC model is an ideal framework for Chinese economy policy analysis. The paper also suggests to incorporate a wider set of state variable, such as monetary, fiscal, and oil price shocks to improve the performance of the model.